Optimizing Employee Performance: A Comprehensive Analysis of Recruitment, Training, and Compensation Strategies - Yulianita Dwi Safitri; Kumara Adji Kusuma (Indonesian Journal of Cultural and Community Development, 2024)
This study investigates the impact of recruitment, training, and compensation on employee performance at a leading manufacturing company. Employing a quantitative approach with an associative focus, the research involved 111 randomly sampled production employees out of a total population of 154. Utilizing the Likert scale, performance was assessed, and data were analyzed through various statistical tests, including validity, reliability, normality, multicollinearity, heteroscedasticity, autocorrelation, and multiple linear regression. The findings reveal that recruitment, training, and compensation each exert a positive and significant influence on employee performance. Furthermore, the simultaneous effect of these factors proves to be collectively substantial. This research contributes valuable insights for organizations aiming to optimize employee performance through strategic human resource practices, emphasizing the interconnected roles of recruitment, training, and compensation. Highlights: The partial tests reveal a positive and significant influence of recruitment, training, and compensation on employee performance. Simultaneous tests affirm the collective positive impact of these factors on performance at PT Harapan Sejahtera Karya Utama. A Likert scale measures employee performance, and the study includes various statistical tests for thorough analysis. Keywords: Recruitment, Training, Compensation, Employee Performance